The wisdom of menopause : creating physical and emotional health during the change - Northrup, Christiane (Bantam Books, 2021)
"Now in its third edition, the groundbreaking, New York Times bestselling classic that has challenged and inspired an entire generation of women with a dramatically new vision of midlife--and that will continue to do so for generations to come. Dr. Christiane Northrup's #1 New York Times bestseller The Wisdom of Menopause has inspired more than a million women with a dramatically new vision of midlife. As Dr. Northrup has championed, the "change" is not simply a collection of physical symptoms to be "fixed," but a mind-body revolution that brings the greatest opportunity for growth since adolescence. The choices a woman makes now--from the quality of her relationships to the quality of her diet--have the power to secure vibrant health and well-being for the rest of her life. Drawing on the current research and medical advances in women's health, the book includes a section on sex after 50--and how, if need be, you can rejuvenate your sex life updated mammogram guidelines--and how thermography improves breast health the latest on the glycemic index, optimal blood sugar levels, and ways to prevent diabetes dietary guidelines revealing that hidden sugar--not dietary fat--is the main culprit in heart disease, cancer, and obesity all you need to know about perimenopause and why it's critical to your well-being a vital program for ensuring pelvic health during and after menopause strategies to combat osteoporosis and strengthen bones for life With this trusted resource, Dr. Christiane Northrup shows that women can make menopause a time of personal empowerment--emerging wiser, healthier, and stronger in both mind and body than ever before"--